Doubly Committed Subarterial Ventricular Septal Defect Coexisted with Ruptured Aneurysm of The Right Sinus Valsava - Irma Maghfirah; Rochmad Romdoni (Cardiovascular and Cardiometabolic Journal, 2022)
Sinus of Valsalva aneurysms (SVAs) are uncommon cardiac abnormalities and most of them are in congenital origin. Some patients may have SVAs that concomitant with ventricular septal defect (VSD). Here, we reported case of a 37-year-old male presented with worsening exertional dyspnoea. Thrills and loud continuous murmur along the left sternal border were discovered during physical examination. Echocardiogram displayed ruptured sinus of valsalva aneurysm to the right ventricle along with supracristal ventricular septal defect (VSD). The patient underwent surgical correction with patch repair and aortic valve replacement. Most cases of SVAs were originated from right coronary sinus. They usually ruptured into right ventricle. Ventricular septal defects often coexisted with this condition. Echocardiography provided a complete evaluation of such cases and prohibited missed diagnosis of other coexistent congenital heart defects. Keywords: Aneurysm of sinus Valsalva, Ventricular septal defect